Efektivitas Latihan Rope Jump dan Hurdle Jump Terhadap Power Tungkai pada Atlet Bola Voli Viking Bajatara - Setiawan, Adi; Apriyanto, Tirto; Dewanti, Rina Ambar (Jurnal Kepelatihan Olahraga, 2024)
This study aims to determine 1. Rope Jump training can increase leg power in volleyball athletes, 2. Hurdle Jump training can increase leg power in volleyball athletes, 3. The effectiveness of Hurdle Jump training compared to Rope Jump training to increase leg power in volleyball athletes. The research method used is the experimental method. The research sample was 32 Viking Bajatara volleyball club athletes. The sampling technique is total sampling. The data processing technique is based on a hypothesis that is tested by parametric statistics using the t-test to determine which experimental class has a higher average. The calculation results obtained a value of ????0 or ????ℎ???????????????????? of 2.77 and a value of ???????????????????????? of 1.69 with a significance level of 5%. the results of the study showed that training with the Hurdle Jump method was more effective than the Rope Jump training method. Based on data analysis, it can be concluded that 1. The Rope Jump training method can improve the jumping results of Viking Bajatara volleyball athletes, 2. The Hurdle Jump training method can improve the jumping results of Viking Bajatara volleyball athletes, 3. The Hurdle Jump training method is more effective than the Rope Jump training method in improving the jumping results of Viking Bajatara volleyball athletes.